Geophysical Surveys at Khirbat Faynan, an Ancient Mound Site in Southern Jordan - Alexandre Novo; Matthew L. Vincent; Thomas E. Levy (International Journal of Geophysics)
Faynan in Jordan contains the largest copper ore resource zone in the southern Levant (Israel, Jordan, Palestinian territories, Lebanon, Syria, and the Sinai Peninsula). Located 50 km southeast of the Dead Sea, it is home to one of the world’s best-preserved ancient mining and metallurgy districts encompassing an area of ca. 400 km2. During the past three decades, archaeologists have carried out numerous excavations and surveys recording hundreds of mines and sites related to metallurgical activities that span the past 10 millennia. Khirbat Faynan (Biblical Punon), is situated in the main Faynan Valley and is the largest (ca. 15 ha) settlement site in the region and has remained unexcavated until 2011. As Jordan’s most southern mound site with indications of widespread ancient architecture, we employed a suite of noninvasive geophysical survey methods to identify areas suitable for excavation. Earlier geophysical surveys were carried out in the Faynan region by our team in the late 1990s when only EMI (electromagnetic induction) proved successful, but with relatively poor resolution. As reported here, by 2011, improvements in data processing software and 3D ERT (electrical resistivity tomography) sampling protocols made it possible to greatly improve the application of noninvasive geophysical surveying in this hyperarid zone.